2022
DOI: 10.1002/nau.25080
|View full text |Cite
|
Sign up to set email alerts
|

Association between urethral funneling in stress urinary incontinence and the biological properties of the urethral rhabdosphincter muscle based on shear wave elastography

Abstract: Objectives: To apply shear wave elastography (SWE) combined with transperineal ultrasonography (TPUS) to study the association between urethral funneling in stress urinary incontinence (SUI) and the biological properties of the urethral rhabdosphincter muscle in women. Methods: This single-center retrospective study included 166 women with SUI (SUI group) and 185 women who underwent a routine physical examination (control group). The control group and SUI group were divided into nonfunneling and funneling grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Wang et al reported that vacuum assisted delivery causes urethral sphincter injury leading to inability to relax the sphincter hence causing urinary retention 18. In our study there were 82(68.3%) cases with age ≤30 years and 38(31.7%) with age >30 years.…”
mentioning
confidence: 44%
“…Wang et al reported that vacuum assisted delivery causes urethral sphincter injury leading to inability to relax the sphincter hence causing urinary retention 18. In our study there were 82(68.3%) cases with age ≤30 years and 38(31.7%) with age >30 years.…”
mentioning
confidence: 44%